C‐kit‐negative transmural gastrointestinal stromal tumor in the stomach: A rare case of upper GI bleeding in Ghana - Samuel Mensah; Ishmael Kyei; Collins Kokuro; Collins Afriyie; Michael Nortey; Ernest Agyei (Clinical Case Reports, 2023)
Abstract Upper GI bleeding from GIST is rare in Africa. The C‐kit‐negative variant is uncommon worldwide. We report a case of a 42‐year‐old woman managed for upper GI bleeding secondary to stomach GIST, negative for CD117 but positive for DOG 1 and CD 34. The 1‐year postsurgery review is uneventful.